Integration of DNA fragments by illegitimate recombination in Saccharomyces cerevisiae. - Robert H. Schiestl; T D Petes (1991)
DNA fragments (generated by BamHI treatment) with no homology to the yeast genome were transformed into Saccharomyces cerevisiae. When the fragments were transformed in the presence of the BamHI enzyme, they integrated into genomic BamHI sites. When the fragments were transformed in the absence of the enzyme, they integrated into genomic G-A-T-C sites. Since the G-A-T-C sequence is present at the ends of BamHI fragments, this results indicates that four base pairs of homology are sufficient for some types of mitotic recombination.